Tari Kreasi Babangsai Babanjaran di Sanggar Labastari Kandangan - Mahdiansyah Mahdiansyah (Program Studi Pendidikan Seni Pertunjukan FKIP ULM, 2016)
AbstractThis study aims to determine the form of presentation of dance creations Babangsai Bakanjaran terms of the motion structure, musical accompaniment, makeup-fashion, property and the venue. The object of research is descriptive qualitative art gallery Labastari Kandangan in Hulu Sungai Selatan, South Kalimantan Province. Data collection techniques using field observations, interviews and documentation. Based on the survey results revealed that the form of presentation of dance creation Babangsai Bakanjaran motion that has a structure of early motion, motion climax and final movements. Musical accompaniment using isntrumen music like saron, a large baboon, baboon small, luma, Sundanese harp, flute and gongs. Character dressing dancers are beautiful women and handsome men. Clothing female dancers use a skirt, dress spangle, headbands, earrings (bunil), while the male dancers fashion model pants, shirt, belt elongation and laung Banjar. The property used is gandang dayak and karimpit. The venue is flexible or can dance anywhere, to the extent where the show is easily accessible to the audience.Keywords: forms of presentation, structure movement, dance creations, babangsai bakanjaran